Self-Esteem As Correlate Of English Language Academic Performance Of Pupils With Intellectual Disabilities In Abakaliki Ebonyi State, Nigeria - Nnenne Oluka, Beth; Augustina Nnenna , Awoke; Annah Chinyeaka, Uloh-Bethels; Terkula Joseph, Chia; Amaka Bibian, Ezeanwu; Ujebe, Nome; Precious Chidimma, Amos; Nancy Nkechi, Amaechi; Michael Nwankwo, John; Nkechi Imakwu, Veronica; Okechukwu Aleke, Christian (CV. Inara, 2025)
Pupils with intellectual disabilities often face challenges in achieving academic success, and low self-esteem may contribute to this struggle. While self-esteem is recognized as an important factor for academic achievement, its specific impact on pupils with intellectual disabilities remains underexplored. This study examined self-esteem as correlate of academic performance of pupils with intellectual disabilities in some schools in Ebonyi State, Nigeria. A purposive sampling technique was employed to select 22 pupils with intellectual disabilities in schools. Instrument for Data collection was a structured questionnaire titled Self-Esteem and Academic Performance of Pupils with Intellectual Disabilities (SEAPPID). Academic performance data were obtained from cumulative English language results. Data were analyzed using descriptive statistics and Pearson Product Moment Correlation (PPMC). Findings indicated that pupils with higher self-esteem performed better academically and were more engaged in their studies. Furthermore, while girls showed slightly better emotional control and focus, gender differences in academic performance were minimal. Based on these findings, it is recommended that teachers adopt strategies that actively promote self-esteem in both male and female pupils with intellectual disabilities. Parents should be encouraged to play a more active role in supporting their children’s self-esteem and academic growth by collaborating with teachers to strengthen learning outcomes. Promoting self-esteem is essential for improving academic performance and fostering resilience in pupils with intellectual disabilities.